Automatic geometry calibration for multi‐projector display systems with arbitrary continuous curved surfaces. Issue 7 (25th April 2019) - Wang, Xiuhui; Yan, Ke; Liu, Yanqiu
Abstract : A large‐scale multi‐projector display system offers high‐resolution, high‐brightness and immersive visualisation for realistic experience to end users. It has been demonstrated to be effective tackling the conflict between the increasing demands of super‐resolution display and the resolution limitation of a single display system. However, there is still no standardisation method for curved‐surface projection screen. In this study, we propose a novel approach for calibrating multi‐projector display systems, which have curved surfaces. First, based on a detailed analysis on arbitrarily curved surfaces, we present a three‐dimensional reconstruction algorithm based on Bezier surface models. Then, for fully utilising the projection area of each projector, we propose a novel curved‐surface stitching algorithm to achieve geometry seamlessness of multi‐projector display systems. Experimental results show that by constructing local Bessel models for the curved screen, the proposed method performs better than traditional approaches, i.e. the new method achieves geometric calibration with higher accuracy. The proposed method of modelling projection screen and the corresponding automatic geometric correction scheme effectively increase the utilisation ratio of the original projection area of each projector and improve the calibration accuracy of multi‐projector system with continuous curved surface.